Isometric knee-extensor torque development and jump height in volleyball players - de Ruiter, C. C.; Vermeulen, G.; Toussaint, H. M.; de Haan, A. (Medicine & Science in Sports & Exercise, 2007)
Purpose: The goal of the present study was to determine the contribution of the intrinsic muscle properties and muscle activation of the knee extensors to the maximal rate of unilateral isometric torque development and to relate both factors to maximal bilateral jumping performance in experienced jumpers. On the basis of previous studies, we hypothesized that maximal rate of torque development during maximal effort isometric contractions and jump height would depend on the subjects' ability for maximal muscle activation rather than on the muscle's contractile properties.